PENGARUH PEMBERIAN VERMIKOMPOS TERHADAP PERTUMBUHAN DAN PRODUKSI PAKCOY (Brassica rapa L.) - Alribowo ' '; Sampoerno ' '; Edison ' Anom (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
Pakcoy (Brassica few L.) is a type of leafy vegetable crops are very important in Indonesia because it has a high economic value. Pakcoy much in demand as a vegetable because of high nutrient content and it tastes good. Pakcoy organic cultivation by using vermicompost can be used as a good alternative considering the potential of earthworm droppings as organic material has a relatively high nutrient content. This study aimed to determine the effect of vermicompost with various doses and got the best dose of the growth and production pakcoy. This study was conducted experimentally using a completely randomized design (CRD) with a dosage of vermicompost (V), which consists of 5 levels ie: V0= tanpa vermicompost (control),V1= vermicompost 1 kg / plot (10 ton/ha),V2= vermicompost 2 kg/plot (20 ton/ha),V3= vermicompost 3 kg/plot (30 ton/ha),V4= vermicompost 4 kg/plot (40 ton/ha). Each treatment consisted of 5 replicates so obtained 25 experimental unit. Each experimental unit, there are 16 plants and four plants including a plant sample randomly determined. Data of variance test later in ujilanjut with Duncan's New Multiple Range Test (DNMRT) at 5% level. The results showed that administration of Vermicompost can promote the growth and crop production pakcoy. Vermicompost at a dose of 4 kg/plot (40 ton/ha) have a better ability to increase growth and crop production pakcoy namely the fresh weight 622 g / plot, and plant fresh weight of 118.4 g unfit for consumption. Keywords: Pakcoy, Vermicompost, soil inceptisol